IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAR - Topik Topik (CV. ADIBA AISHA AMIRA, 2023)
In science education consists of three very main aspects, namely; science as a product, science as a process, and science as a scientific attitude. In learning science itself, sometimes students still do not understand the value of a scientific attitude which results in an imperfect process of scientific nature and a lack of forming students' scientific attitudes. Viewed academically, character education is a value education, character education, moral education, character education which aims to develop students' ability to give good and bad character, so that these actions can be implemented in everyday life. Therefore, character education that is based on juridical values contains the standard competency standards of graduates in an educational institution, especially Elementary Schools (SD). Integrating the development of character culture with science education can be done with several strategies including the application of the Thinking Ability and Thinking Strategy Model (KBSB), in which this model integrates thinking skills and thinking strategies in the activities carried out by students. A culture of Thinking Ability and Thinking Strategies will be a starting point in shaping students with character so that their skills and attitudes can understand their natural environment. In addition, character education can also be implemented in science education in the habituation of daily life in educational units which will be integrated into extracurricular activities so that the character culture of students will become habituation in everyday life.